'Take more laxatives was their answer to everything': A qualitative exploration of the patient, carer and healthcare professional experience of constipation in specialist palliative care. (September 2020) - Hasson, Felicity; Muldrew, Deborah; Carduff, Emma; Finucane, Anne; Graham-Wisener, Lisa; Larkin, Phil; Mccorry, Noleen; Slater, Paul; McIlfatrick, Sonja
Background: Constipation is a major problem for many older adults, more so for those who are receiving specialist palliative care. However, limited research reports the subjective experiences of constipation, despite evidenced differences between the healthcare professional and patient/carer perspective. Aim: The main aim of this study is to explore the experience of how constipation is assessed and managed within specialist palliative care from the patient, carer and healthcare professional perspective. Design: Exploratory, qualitative design, utilising focus groups and interviews, and analysed using thematic analysis. Setting/participants: Six focus groups with 27 healthcare professionals and semi-structured interviews with 13 patients and 5 family caregivers in specialist palliative care units across three regions of the United Kingdom. Results: Constipation impacted physically, psychologically and socially on patients and families; however, they felt staff relegated it on the list of importance. Lifestyle modifications implemented at home were not incorporated into their specialist palliative care plan within the hospice. Comparatively, healthcare professionals saw constipation solely as a physical symptom. Assessment focused on the physical elements of constipation, and management was pharmacologically driven. Healthcare professionals reported patient embarrassment as a barrier to communicating about bowel care, whereas patients wanted staff to initiate communication and discuss constipation openly. Conclusion: Assessment and management of constipation may not yet reflect the holistic palliative care model. A focus on the pharmacological management may result in lifestyle modifications being underutilised. Healthcare professionals also need to be open to initiate communication on bowel care and consider non-pharmacological approaches. It is important that patients and families are supported in self-care management, alongside standardised guidelines for practice and for healthcare professionals to facilitate this.